1. Podstawowe wskaźniki makroekonomiczne Kirgistanu, główne działy gospodarki i polityka ekonomiczna po 2010 roku .......... 85 - Rabiasz, Łukasz (Kirgistan – oblicza transformacji, 2020)
KYRGYZSTAN’S ECONOMY AFTER 2010. CONTINUATION OF PREVIOUS TRENDSThe purpose of the article is to present and analyze the state of the economy and economic policy of the Republic of Kyrgyzstan after 2010. After regaining independence, Kyrgyzstan, unlike other countries in the region, carried out reforms aimed at shifting from planned economy to the market model. The country has become a Central Asian experimental training ground for economic transformation. However, the reforms have not been completed and subsequent governments which took power after 2010 did not put the country on track for faster economic growth.